Improvement in Manufacturing of Aluminium-Based Functionally Graded Materials through Centrifugal Casting—A Review - S. Prathap Singh; R. P. Rohith; S. Franklin Nirmal; D. Elil Raja; P. Ravichandran (Engineering Proceedings, 2024)
The global demand for functionally graded materials (FGMs) has grown rapidly. This research reviews FGMs and the production technologies that affect their physical, structural, and manufacturing properties. We discuss the aluminium alloys and ceramics used in the fabrication process based on their engineering uses in many industries. Centrifugal casting is the versatile and commercial viable method to manufacture FGMs. These FGMs possess a variety of applications in automobile and aerospace industries owing to their enhanced mechanical strength and thermal and corrosion resistance.